An Exotic Species Is the Favorite Prey of a Native Enemy - Li, Yiming; Ke, Zunwei; Wang, Supen; Smith, Geoffrey R.; Liu, Xuan (PLOS ONE, 2011)
Although native enemies in an exotic species' new range are considered to affect its ability to invade, few studies have evaluated predation pressures from native enemies on exotic species in their new range. The exotic prey naiveté hypothesis (EPNH) states that exotic species may be at a disadvantage because of its naïveté towards native enemies and, therefore, may suffer higher predation pressures from the enemy than native prey species. Corollaries of this hypothesis include the native enemy preferring exotic species over native species and the diet of the enemy being influenced by the abundance of the exotic species. We comprehensively tested this hypothesis using introduced North American bullfrogs (Lithobates catesbeianus, referred to as bullfrog), a native red-banded snake (Dinodon rufozonatum, the enemy) and four native anuran species in permanent still water bodies as a model system in Daishan, China. We investigated reciprocal recognition between snakes and anuran species (bullfrogs and three common native species) and the diet preference of the snakes for bullfrogs and the three species in laboratory experiments, and the diet preference and bullfrog density in the wild. Bullfrogs are naive to the snakes, but the native anurans are not. However, the snakes can identify bullfrogs as prey, and in fact, prefer bullfrogs over the native anurans in manipulative experiments with and without a control for body size and in the wild, indicating that bullfrogs are subjected to higher predation pressures from the snakes than the native species. The proportion of bullfrogs in the snakes' diet is positively correlated with the abundance of bullfrogs in the wild. Our results provide strong evidence for the EPNH. The results highlight the biological resistance of native enemies to naïve exotic species.